Colloidal Self-Assembled Patterns Maintain the Pluripotency and Promote the Hemopoietic Potential of Human Embryonic Stem Cells - Lin, Jiao; Zeng, Jiahui; Sun, Wencui; Liu, Kun; Enkhbat, Myagmartsend; Yi, Danying; Harati, Javad; Liu, Jiaxin; Kingshott, Peter; Chen, Bo; Ma, Feng; Wang, Peng-Yuan (Frontiers in Cell and Developmental Biology, 2021)
The generation of blood cells in a significant amount for clinical uses is still challenging. Human pluripotent stem cells-derived hemopoietic cells (hPSC-HCs) are a promising cell source to generate blood cells. Previously, it has been shown that the attached substrates are crucial in the maintenance or differentiation of hPSCs. In this study, a new family of artificial extracellular matrix (ECM) called colloidal self-assembled patterns (cSAPs: #1-#5) was used to expand mouse and human PSCs. The optimized cSAP (i.e., #4 and #5) was selected for subsequent hemopoietic differentiation of human embryonic stem cells (hESCs). Results showed that the hematopoietic potential of hESCs was enhanced approx 3-4 folds on cSAP #5 compared to the flat control. Furthermore, the cell population of hematopoietic progenitors (i.e., CD34+CD43+ cells) and erythroid progenitors (i.e., CD71+GPA+ cells) were enhanced 4 folds at day 8 and 3 folds at day 14. RNA sequencing analysis of cSAP-derived hESCs showed that there were 300 genes up-regulated and 627 genes down-regulated. The enriched signaling pathways, including up-regulation (i.e., Toll-like receptor, HIF-1a, and Notch) or down-regulation (i.e., FAs, MAPK, JAK/STAT, and TGF-β), were classic in the maintenance of hESC phenotype. Altogether, c SAP enhances the pluripotency and the hematopoietic potential of hESCs that subsequently generates more blood-like cells. This study reveals the potential of cSAPs on the expansion and differentiation of stem cells. cSAP is a next-generation material for early-stage blood cell lineage differentiation of hPSCs.